Suppressor of Cytokine Signaling 3 (SOCS3) Degrades p65 and Regulate HIV-1 Replication - Sood, Vikas; Lata, Sneh; Ramachandran, Vishnampettai G.; Banerjea, Akhil C. (Frontiers in Microbiology, 2019)
Human Immunodeficiency Virus-1 (HIV-1) is known to induce the expression of SOCS3 which is a negative feed-back regulator of inflammatory responses. Here, we demonstrate that reactivation of latent HIV-1 leads to degradation of SOCS3 at early time points. Interestingly, SOCS3 degradation following transfection of HIV-1 RNA as well as polyIC in THP-1 cells pointed towards the role of RNA sensing and signaling in SOCS3 biology. Further investigations revealed that SOCS3 inhibits the expression and activity of p65 by interacting with it and inducing its ubiquitin-dependent proteasomal degradation. SH2 domain of SOCS3 was critical for SOCS3-p65 interaction and p65 degradation. We also found that expression of SOCS3 promotes HIV-1 replication. Thus, HIV-1 downregulates SOCS3 in early phase of infection to promote inflammatory responses for large production of activated cells which are suitable for viral spread and induces SOCS3 later on to limit inflammatory responses and ensure viral survival.